If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+1=3x+13
We move all terms to the left:
2x+1-(3x+13)=0
We get rid of parentheses
2x-3x-13+1=0
We add all the numbers together, and all the variables
-1x-12=0
We move all terms containing x to the left, all other terms to the right
-x=12
x=12/-1
x=-12
| 4.50.25a+0.5=4.5 | | 2x+1=3×+13 | | -21=s-17 | | -2r=-r+11 | | 6(y+3)+3=9 | | 10(x−1)=5(x+2) | | 8h-12=6h | | 3x+9=8x+14 | | t-10/4=-4 | | 17+w=19 | | t–104=-4 | | -5a+10a=10 | | -4=2(s+5) | | 1=-6z+5z | | 5(x+3)–3x=55 | | 69=-391+4x | | 18=7r+18 | | 2(y-6)+3=2y-7 | | 15x=69.6 | | 7n^2+10=-19n | | 18+7r=18 | | -2x+1=3x-4 | | 4x-3-3(2x)=12+3x | | (2x+15)+6=180 | | 50=-8z-2z | | 50=-8z–2z | | 3(u+3)=15 | | u/5+8=38 | | 9x-14=25 | | f(-4)=3(-4)-2 | | 7t+4=102−7t | | 5(z-2)+3z=1 |